Relationships Between University Characteristics and Early Job Outcomes of Accountants - Colarelli, Stephen M.; Dean, Roger A.; Konstans, Constantine (Canadian Journal of Higher Education, 1991)
This study undertook an examination of relationships among university characteristics and job offers, employment status, job attitudes, and job performance of newly-hired accounting graduates. It was found that university characteristics are generally not related to job attitudes and job performance. A few characteristics correlated with the total number of job offers, and characteristics associated with wealth and status correlated with receiving job offers from prestigious accounting firms. Several explanations are suggested for the results—including threshold effects, prestige effects, and influence of the work environment.